Distinguish - García-Yzaguirre, Víctor (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
This article advances a precise conceptualization of distinguish, drawing on the leading theories of precedent that operate within the rule-based model. It therefore presupposes a precedent system that grants legal decision-makers the competence to depart from prior rulings when specific conditions obtain. Within this framework, the power to distinguish is shown not to weaken the authority of precedents; rather, it enables the correction of errors and preserves the normative predictability required by legal certainty. To develop the argument, section 2 outlines the general features of distinguishand clarifies the operations and practical outcomes it entails, while section 3 reconstructs the potential limits on its exercise, identifying the criteria that may legitimately justify a distinguish from a precedent.
Keywords: precedents; distinguish; interpretation; exceptions; validity